2016
DOI: 10.5942/jawwa.2016.108.0014
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Unit Hydrograph Development for Ungauged Basins Using Dimensional Analysis

Abstract: The authors set out to determine average representative unit hydrographs (UHs) for the upper Kumbhi basin and the Dhamani basin in Maharashtra, India, from selected isolated storms. They developed an innovative approach using dimensional analysis techniques to establish an empirical model to determine synthetic UH (SUH) parameters for the upper Kumbhi basin. This method was used to select proper empirical relationships for SUH analysis for the ungauged basins with similar hydrological conditions. Results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For SW3, the values of t p , t b and Q p were 12.07 h, 32.21 h and 55.32 m 3 /s. Patel & Thorvat (2016) had worked on the different SUH methods at the Upper Kumbhi Basin and the Dhamani Basin, Maharashtra, India. They found that Mitchell's method is provided with a percentage error of 11.361% (still within the range of error) for the study area.…”
Section: Mitchell's Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For SW3, the values of t p , t b and Q p were 12.07 h, 32.21 h and 55.32 m 3 /s. Patel & Thorvat (2016) had worked on the different SUH methods at the Upper Kumbhi Basin and the Dhamani Basin, Maharashtra, India. They found that Mitchell's method is provided with a percentage error of 11.361% (still within the range of error) for the study area.…”
Section: Mitchell's Methodsmentioning
confidence: 99%
“…Salami et al (2009) had summarised that the SCS method was best for eight rivers in South-West, Nigeria. Patel & Thorvat (2016) found that Mitchell's method gives an acceptable percentage error for the Upper Kumbhi Basin and the Dhamani Basin, Maharashtra, India. Salami et al (2017) again recommended the SCS method to estimate the ordinate required to develop peak runoff hydrograph for Ogun-Osun river catchment, south-west, Nigeria.…”
Section: Introductionmentioning
confidence: 94%
“…Having chosen the length of the main channel and the duration of effective rainfall as the repeating variables, they obtained four dimensionless pi groups. As the outcome, Patel and Thorvat (2016) derived analytical expressions for peak flow rate (Qp), time to peak (tp), and time base (tb) of the synthetic unit hydrograph in terms of the area of the watershed (A), the length of main channel (L), the length of main channel between the outlet and the center of gravity of the watershed (Lc), the average slope of the main channel (S), and rainfall duration (tr). They applied this method to two fairly small watersheds of sizes 122 and 156 km 2 in India for tr = 1 h. They compared various peculiarities such as the peak flow rate and time to peak of the synthetic unit hydrographs by their method with those given by four other methods two of which were Snyder and SCS (Patel and Thorvat 2016).…”
Section: New Approaches For the Synthetic Unit Hydrographmentioning
confidence: 99%
“…The parameters of these analytical equations are determined so as to make the ratio of the volume of the synthetic unit hydrograph, which is computed numerically by the trapezoidal rule, to the drainage area equal 1 cm (Natakusumah et al 2013). Patel and Thorvat (2016) developed a new synthetic unit hydrograph method as the outcome of applying the classical Buckingham pi theorem of dimensional analysis. Having chosen the length of the main channel and the duration of effective rainfall as the repeating variables, they obtained four dimensionless pi groups.…”
Section: New Approaches For the Synthetic Unit Hydrographmentioning
confidence: 99%